A Conjoint Analysis of Student Preferences for Teaching and Learning Process - Utami, Septiana Dwi; Masiah, Masiah; Firdaus, Laras; Primawati, Sri Nopita; Royani, Ida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Assessments carried out by education quality monitoring institutions often ignore student assessments, the results of which are not relevant to what students need. Therefore, the assessment of the teaching and learning process must be carried out transparently and accountable by involving students in the assessment of teaching and learning process. Actions like this are nothing more than an effort to adapt the teaching and learning process to student needs. This descriptive research aims to explain students' preferences for the quality of teaching and learning. A total of 65 prospective biology teachers were respondents, consisting of 17 students in 1st semester, 23 (3rd semester), 7 (5th semester), and 18 (7th semester). From the results obtained, our respondents consider that increasing competence is the most essential attribute or factor related to the teaching and learning process, with an important value percentage of 21.931. Then, teaching organizations (19.901) and learning opportunities (19.662). We use this information regarding student preferences as a guide to improving the teaching and learning process in the future while still correcting several existing deficiencies, such as involving active student participation and providing maximum academic assistance, as well as allowing students to develop their thinking abilities.